Research on the Method of Determining the Optimum Microtexture Parameters of Ballend Mill - YANG Shu-cai; MA Xu-qing; ZHANG Yu-hua; LIU Wei-wei; HE Chun-sheng (Journal of Harbin University of Science and Technology)
In order to study the influence of microtexture on the cutting performance of ballend milling, and to complete the optimization of micro texture parameters, the frictionreducing and wearresistant mechanism of microtexture ballend milling was studied based on the theory of adhesive friction The experimental method was used to verify the correlation The finite element software DEFORM3D was used to simulate the milling of different texture parameters, and the reasonable range of tool microtexture parameters was obtained According to the range of parameters obtained from the simulation, an orthogonal test was designed to optimize the optimal texture parameters of the ballend cutter to be D=50μm、H=25μm、L1=130μm、L2=110μm